PENGARUH PENGAWASAN TERHADAP PRODUKTIVITAS KARYAWAN (Kasus Karyawan Bagian Produksi PT. P&P Bangkinang) - Yazid Ardiansyah; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Problems in the research is still lack of supervision conducted by the company tothe employees of the production, so it's still widespread illegalities that occurred asemployees who work not in accordance with standards and instructions given bysuperiors. Besides not the achievement of a target production in the last two years,indicating a lack of employee productivity in your work. As for the purpose of research isto find out the supervision, employee work productivity as well as know how theoversight of employee productivity part production at PT. P&P Bangkinang.. Results ofthe study concluded that surveillance against employees of the production at PT. P&Pbeen rated good Bangkinang, just that there is still a lot of shortcomings perceived bythe employees, so still there deviations in the works. Employee productivity partproduction at PT. P&P Bangkinang votes already, but there are also still manyshortcomings such as the lack of professionalism of employees in work. Analysis withSPSS obtained results that surveillance has a strong relationship to the productivity ofemployees work part of production at PT. P&P Bangkinang. The positive effect of thesupervisory employee productivity, so any improvement of supervision, it will be able toincrease the productivity of employees work part of production at PT. P&P Bangkinang.Keywords: supervision, productivity, PT. P&P bangkinang